Depression in persons with disabilities: a scoping review - Asdaq, Syed Mohammed Basheeruddin; Alshehri, Sultan; Alajlan, Sarah Abdulrahman; Almutiri, Abdulaziz Ali; Alanazi, Abdullah Khatim R. (Frontiers in Public Health, 2024)
Individuals with disabilities are more vulnerable to depression development than the general population. This study sought to map the evidence on current knowledge of depression, intervention strategies, and assessment tools among people with disabilities. This review was conducted following Arksey and O′Malley’s scoping review methodology framework. An electronic search was performed on four English databases: PubMed, Cochrane Library, PsycINFO, and Web of Science. The original search returned 1802 results, with 1,116 from Web of Science, 626 from PubMed, 25 from Cochrane, and 35 from PsycINFO. After removing duplicates, 786 articles were chosen for the title and abstract screening processes. Finally, 112 full-text publications were deemed eligible, with 41 papers being included in this scoping review for analysis. A large proportion (32; 78.04%) of the studies chosen were cross-sectional, 14 (34.14%) of them reported general disability, 12 (29.26%) used a patient health questionnaire (PHQ-9) to measure depression, and 14 (34.14%) had interventions, including cognitive behavioral therapy, psychological counseling, social support, and physical activity. All interventions successfully reduced the severity of the depression. Cognitive behavioral therapies and psychological counseling were widely used interventions that had a significant impact on reducing depression. More randomized controlled trials are required, and they should focus on individuals with specific disabilities to provide disability-specific care that can improve the quality of life for disabled individuals.